Practical psychotherapy with adolescents - Rubenstein, Alice K.; Broderson, Gene; Frank-McNeil, Julia; American Psychological Association (Washington, DC : American Psychological Association, 1996)
Presents a case study and demonstration of psychotherapy with an adolescent having behavioral problems. Alice K. rubenstein demonstrates her approach to working with adolescent clients. Helps adolescent clients to identify their feelings and identify their feelings and the factors contributing to the problems they are dealing eith, and then help brainstorm possible situation
Title from title screen
Narrator: Doug Fizel
Keywords: Teenagers -- Counseling of; Psychotherapy; Adolescent psychiatry; Adolescent psychology